2013
DOI: 10.1175/jas-d-12-0129.1
|View full text |Cite
|
Sign up to set email alerts
|

The Troposphere-to-Stratosphere Transition in Kinetic Energy Spectra and Nonlinear Spectral Fluxes as Seen in ECMWF Analyses

Abstract: Global horizontal wavenumber kinetic energy spectra and spectral fluxes of rotational kinetic energy and enstrophy are computed for a range of vertical levels using a T799 ECMWF operational analysis. Above 250 hPa, the kinetic energy spectra exhibit a distinct break between steep and shallow spectral ranges, reminiscent of dual power-law spectra seen in aircraft data and high-resolution general circulation models. The break separates a large-scale ''balanced'' regime in which rotational flow strongly dominates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 35 publications
22
61
0
Order By: Relevance
“…6a which represents the vertically integrated total energy is not simple. Blažica et al (2013) showed that on mesoscale in midlatitudes the divergent component of kinetic energy is at least equally as large as the rotational component and that the slopes of the corresponding spectra depend on the altitude (see also Burgess et al, 2013). In our global case with the tropics dominated by divergent circulations, we find that the unbalanced component makes up 80 % or more of the total energy beyond zonal wave number 100 (about 150 km in midlatitudes) (Fig.…”
Section: Scale-dependent Energy Distributionsupporting
confidence: 56%
See 1 more Smart Citation
“…6a which represents the vertically integrated total energy is not simple. Blažica et al (2013) showed that on mesoscale in midlatitudes the divergent component of kinetic energy is at least equally as large as the rotational component and that the slopes of the corresponding spectra depend on the altitude (see also Burgess et al, 2013). In our global case with the tropics dominated by divergent circulations, we find that the unbalanced component makes up 80 % or more of the total energy beyond zonal wave number 100 (about 150 km in midlatitudes) (Fig.…”
Section: Scale-dependent Energy Distributionsupporting
confidence: 56%
“…Furthermore, energy spectra derived from models are usually based on single level data (e.g. Burgess et al, 2013;Blažica et al, 2013) and they show only kinetic energy; correspondingly, their comparison with the spectrum in Fig. 6a which represents the vertically integrated total energy is not simple.…”
Section: Scale-dependent Energy Distributionmentioning
confidence: 99%
“…Below 150 km, the slope of E DIV spectrum is close to (1.8 while the E VOR spectrum has a slope about (2. For larger scales, the difference between the slopes of divergent and rotational spectra is clearly increasing as the horizontal scale becomes larger as found in the global model data studied by Burgess et al (2013) and in the analysis of global rotational and inertio-gravity energy by Zagar et al (2009Zagar et al ( , 2010.…”
Section: Horizontal Spectramentioning
confidence: 65%
“…Koshyk et al (1999) showed that in several general circulation models divergent and rotational kinetic energy are about equally important in the stratosphere and the mesosphere while in the upper troposphere rotational energy is dominant. A recent evaluation of the European Centre for MediumRange Weather Forecasts (ECMWF) model spectra at T799 resolution by Burgess et al (2013) shows that at 200 hPa global divergent energy becomes prevalent over global rotational energy at 400 km whereas above 100 hPa divergent component is dominant over rotational component across all scales smaller than Â1200 km (global wavenumber Â30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation